Biocompatible photoinduced CuAAC using sodium pyruvate. Issue 95 (17th November 2021) - Jeong, Jaepil; Szczepaniak, Grzegorz; Yerneni, Saigopalakrishna S.; Lorandi, Francesca; Jafari, Hossein; Lathwal, Sushil; Das, Subha R.; Matyjaszewski, Krzysztof
Abstract : The use of sodium pyruvate as a photoreducing agent for copper-mediated azide–alkyne cycloaddition (CuAAC) under UV irradiation is described. Abstract : Sodium pyruvate, a natural intermediate produced during cellular metabolism, is commonly used in buffer solutions and media for biochemical applications. Here we show the use of sodium pyruvate (SP ) as a reducing agent in a biocompatible aqueous photoinduced azide–alkyne cycloaddition (CuAAC) reaction. This copper(i )-catalyzed 1, 3-dipolar cycloaddition is triggered by SP under UV light irradiation, exhibits oxygen tolerance and temporal control, and provides a convenient alternative to current CuAAC systems, particularly for biomolecular conjugations.